Torrance's future problem-solving instruction: Developing students' problem-solving ability - Duangrawa, Asanlaya; Nuangchalerm, Prasart (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
The purpose of this research was to develop the problem-solving ability of grade 10th students by using Torrance’s future problem-solving instruction. The researchers used action research in this study. The target group consisted of fifteen 10th-grade students of the second semester in the 2019 academic year. Students who had problem-solving ability scores in low criteria showed lower than 70% of the full score. This study's research instruments were four lesson plans in the topic energy, problem-solving ability tests, observation form of problem-solving ability during lesson plans implementation, and students’ interviewing form in problem-solving ability. Data were collected and analyzed by descriptive statistics. The finding showed that the problem-solving ability score of the target group increased in each action cycle. At the end of the fourth cycle, the problem-solving ability score of all students was above 70%. According to the results, Torrance's future problem-solving instructional model can help students improve their problem-solving ability.